ISSUES OF TERMINOLOGY: Kuliyeva Dilshoda Alijon qizi, Ganiyeva Muxtasarxon Muxtorjon qizi - Teacher of the Faculty of World Languages (English), Kuliyeva Dilshoda Alijon qizi; Namangan State University, Faculty of World Languages (English), Ganiyeva Muxtasarxon Muxtorjon qizi (Лучшие интеллектуальные исследования, 2024)
When studying terminological vocabulary, the heterogeneity of its composition in terms of the characteristics of the conceptual content of various units becomes obvious, which is reflected in the creation of various classifications of terminological vocabulary, some of which will be discussed in this section.